Perlawanan dalam Puisi Peringatan Karya Wiji Thukul : Telaah Semiotik Roland Barthes - Budi Hartono; Masnita Massaguni (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the poem "Peringatan" ("Warning") by Wiji Thukul using Roland Barthes' semiotic theory. The aim of the research is to uncover the meaning of resistance implied in the poem through three layers of meaning: denotative, connotative, and myth. The poem was written in a repressive socio-political context, in which freedom of expression was silenced by those in power. Through a Barthesian approach, the lines of the poem are analyzed as a system of signs that symbolically represent resistance against authoritarian rule. The analysis reveals that the poem not only conveys an aesthetic message but also constructs a counter-discourse to the dominant ideology. The poem becomes a site of resistance, urging the people not to submit to oppression. This study reinforces the view that literature, particularly poetry, holds great potential as a medium of struggle and freedom.